2015
DOI: 10.7314/apjcp.2015.16.14.5721
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variation in Consumption of Traditional Tobacco Products and Lung Cancer Risk in Nepal

Abstract: Lung cancer is the leading contributor to cancer deaths in the developing world. Within countries, significant variability exists in the prevalence of lung cancer risk, yet limited information is available whether some of the observed variability is associated with differences in the consumption pattern of local tobacco products with differing potency. We recruited 606 lung cancer cases and 606 controls from the B.P. Koirala Memorial Cancer Hospital in Nepal from 2009-2012. We estimated odds ratios (ORs) and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Despite these limitations, this is one of the few epidemiological studies examining potential lung cancer risk factors in Nepal (30, 31, 48–50), a country with limited cancer research resources and is the first study to examine the relationship between reproductive and hormonal factors and lung cancer among Nepali women. Additionally, studies that have examined the prevalence of reproductive and hormonal factors among Nepali women are scarce, and this study contributes much needed prevalence data on these exposures among Nepali women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, this is one of the few epidemiological studies examining potential lung cancer risk factors in Nepal (30, 31, 48–50), a country with limited cancer research resources and is the first study to examine the relationship between reproductive and hormonal factors and lung cancer among Nepali women. Additionally, studies that have examined the prevalence of reproductive and hormonal factors among Nepali women are scarce, and this study contributes much needed prevalence data on these exposures among Nepali women.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilizes data from a hospital-based case-control study, conducted between November 2009 and December 2012, at the B. P. Koirala Memorial Cancer Hospital (BPKMCH) in the city of Bharatpur, Chitwan district (30, 31). The primary study is described in previous publications (30, 31).…”
Section: Methodsmentioning
confidence: 99%
“…The crude incidence rate of lung cancer is 4.6 per 100,000 populations in Nepal while it was 4.45 in 2012 [ 5 ]. The following mitigating factors may have an effect on this trend: lower education, unmarried individuals and Rai/Limbu/Magar ethnicity [ 10 ], household air pollution and tobacco consumption [ 11 , 12 ], and not enough medical health education [ 13 ]. For young people in western Nepal; smoking was a serious issue [ 14 ] and the risk factor leading to lung cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking prevalence in Vietnam varies by ethnic groups, consistent across other countries. 3,5 Each ethnicity has distinct languages, lifestyles, and social norms, leading to ethnic variation of tobacco use in Vietnam. For example, both Ba Na males and females were keen on using hand-rolling cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of tobacco use was found to vary across ethnic groups in Nepal and Pakistan. 5,6 A study in China has shown that the smoking and drinking prevalence among ethnic minorities is significantly higher than the Han ethnic majority. 7 Vietnam is a multiethnic nation consisting of 54 distinct ethnicities, each with a unique language, lifestyle, and cultural heritage, in which 14.2 million people (accounting for 14.7% of the Vietnamese population) belong to an ethnic minority group.…”
Section: Introductionmentioning
confidence: 99%